Study of Heavy Minerals from the Vjosa and Mati river delta sediments in Albania - Xhaferri, Emiriana; Corijn, Ruben; Sinojmeri, Agim; Swennen, Rudy; Durmishi, Çerçis (Bulletin of the Geological Society of Greece, 2020)
This research is focused on the determination of the heavy minerals (HM) load of the Vjosa and Mati river delta deposits along the Albanian coastline and it is based on X-ray Diffractometry. The Albanian coastline consists of sandy beaches at the north (Adriatic coastline) and rocky escarpments at the south (Ionian coastline). Several layers of heavy mineral deposits, up to 50 cm thick, with heavy mineral fraction up to 95% and 88% of total sample for Vjosa and Mati sediments respectively, are identified. The layers enriched in heavy minerals from Vjosa delta deposits are almost black in colour, while at Mati delta these layers are dark green coloured. Separation of the heavy from the light fraction was performed, in order to compare the different fractions between the two studied delta areas. The accumulation of HM occurs mainly in the fraction of 125-250 µm in the sediments of both deltas. The HM dominate in the magnetic field of 0.4-0.8 A/m. XRD analysis results show a great variety of minerals present in the delta samples which can be attributed to the wide variety of geological zones and lithologies that are intersected by the Vjosa and Mati rivers, respectively. In the 63-425 μm fraction rich in heavy minerals of both delta systems considerable amounts of magnetite (up to 39.4% in Vjosa samples), chromite (up to 20.2% in Vjosa samples), garnet (up to 13.6% in Vjosa samples), ilmenite (up to 8.3% in Mati samples), rutile (up to 4.7% in Mati samples), hematite (up to 2.2% in Mati samples), and zircon (up to 2.1% in Vjosa samples) are observed. Rock forming minerals such as pyroxene, amphibole, and epidote compose significant percentages of this fraction. In addition, the presence of gold grains in Vjosa delta sediments is remarkable. Both catchment areas consist to a great extent of similar formations such as the Mirdita Ophiolite Zone and the Pindos Ophiolite complex, providing thus a similar HM fingerprint at both delta areas. Minerals that occur in higher abundances reflect the extensive presence in the drained areas of related parent rocks which are rich in these minerals and which are often more vulnerable to weathering. The samples of Vjosa river delta show high percentage of carbonate constituents, which is related to the presence of carbonate rocks of the Ionian and Kruja tectonic zones within which the hydrographic network of the Vjosa River has been developed. The samples of Mati river delta show lower abundance of carbonate minerals, reflecting the limited presence of carbonate rocks at the Kruja Zone, which occur in the catchment area of the river near its mouth.